Comparative study of cone-beam computed tomography and multislice computed tomography in the radiographic evaluation of cysts and tumors of the jaws - Sunil S Mishra (Journal of Indian Academy of Oral Medicine and Radiology, 2014)
Aim and Objectives: To assess the efficacy of cone-beam computed tomography (CBCT) in comparison with multislice-computed tomography (MSCT) in the radiographic evaluation of cysts and tumors of the jaws. Materials and Methods: The study was conducted on 25 subjects diagnosed histopathologically with cysts or tumors of the jaws. They were subjected to MSCT and CBCT. The image pairs obtained were compared for diagnostic quality and dimensional accuracy. Also radiation monitoring was done with a newly devised calculative method. Statistics: Descriptive statistical analysis was carried out for all the groups in this study. The Kappa coefficient (k) for intraclass agreement was used for evaluating the scorings given by the evaluator for the diagnostic quality of the image. Results: A total of 28 lesions were found in 25 subjects. The diagnostic quality assessment suggested that the appearance of the internal structure and the soft tissue resolution of CBCT were inferior to MSCT. The radiation dosages from CBCT were noticeably less than MSCT. The dimensional accuracy of CBCT images was found to match those of the MSCT images. Conclusion: The results from the present study showed that CBCT could provide an image with MSCT-comparable diagnostic quality and accuracy, with a lesser radiation dose and risk, at a lower cost.